Validation of HVLT-R, BVMT-R, and RBANS Learning Slope Scores along the Alzheimer's Continuum. (24th April 2021) - Hammers, Dustin B; Suhrie, Kayla; Dixon, Ava; Gradwohl, Brian D; Duff, Kevin; Spencer, Robert J
Abstract: Background: The learning ratio (LR) is a novel learning slope score that has been developed to reduce the inherent competition between the first trial and subsequent trials in traditional learning slopes. In essence, the LR is the number of items learned after the first trial divided by the number of items yet to be learned. Criterion and convergent validation of this LR score is warranted to understand its sensitivity along the Alzheimer's disease (AD) continuum. Method: The LR metric was calculated for 123 participants from standard measures of memory, including the Hopkins Verbal Learning Test—Revised, Brief Visuospatial Memory Test—Revised, Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) list learning, and RBANS story memory. All participants were categorized as normal cognition, mild cognitive impairment (MCI), or AD. LR performances were compared between groups, among other standard memory measures, and with regards to how well they discriminated cognitively impaired from unimpaired samples—and within diagnostic subgroups. Results: Lower LR scores were observed for the MCI and AD groups than the normal cognition group, with the AD group performing worse than the MCI group for several slope calculations. Lower LR scores were also consistently associated with poorer performances on traditional memory measures. LR scores further displayed excellent receiver operator characteristics when differentiating those with and without cognitive impairment—and MCI from normal cognition. Overall, LR scores consistently outperformed traditional learning slope calculations across all analyses. Conclusions: This LR score is sensitive to memory dysfunction along the AD continuum, and results offer criterion and convergent validity for use of the LR metric to understand learning capacity.